The CIN-TCP transcription factors regulate endocycle progression and pavement cell size by promoting cell wall pectin degradation - Feng Shen; He Zhang; Miaomiao Wan; Yanzhi Yang; Zheng Kuang; Liang Xiao; Daqing Zuo; Zhan Li; Genji Qin; Lei Li (Nature Communications)
Abstract In plants, endoreplication, the process where nuclear DNA replicates in the absence of mitosis, and remodeling of the primary cell walls are both coupled with cell expansion. However, the mechanisms by which these two processes coordinate to determine cell size remain largely elusive. Here, employing the tcpΔ7 septuple mutant disabling seven of the eight CIN-TCP transcription factors in Arabidopsis, we find that hindered endoreplication progression in tcpΔ7 whereby ploidy increases from 8 C to beyond is correlated with an increase in cell wall pectin. CIN-TCPs transcriptionally activate POLYGALACTURONASE LIKE 1 (PGL1), which encodes a polygalacturonase downregulating both abundance and molecular mass of pectin polymers. Genetic analysis of PGL1 in both the wild type and tcpΔ7 backgrounds confirm that pectin reduction promotes endocycle progression and cell enlargement. Collectively, these findings reveal a critical role of pectin in regulating endoreplication, providing insights in the understanding of cell growth and organ development in plants.